in vitro Antioxidant Activity and Total Phenolic Content of Various Extracts of Satureja hortensis L. Collected from Turkey - Yesiloglu, Yesim; Sit, Latifsah; Kilic, Ismail (Asian Journal of Chemistry, 2013)
The antioxidant capacities of the acetone, ethanol and water extracts of leaves and flowers of S. hortensis were estimated using different antioxidant tests, including lipid peroxidation, reducing power, 1,1-diphenyl-2-picryl-hydrazyl (DPPH) radical scavenging, iron chelation, superoxide anion radical scavenging and hydrogen peroxide scavenging. The contents of antioxidant components in these extracts were also determined. Results showed that the highest contents of these components including phenols and flavonoids were found in water extract. This study verified that the water extract has strong antioxidant activities which were correlated with its high level of phenolics and flavonoids. This extract can be used as a source of potential antioxidant or functional food material.